GE_GERICHTE P/12777/2012 vom 13. August 2013 - GE Cour de justice (2013)
IN DUBIO PRO REO; FIXATION DE LA PEINE; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE; RÉVOCATION DU SURSIS | CPP.10.3; CP.42; CP.43; CP.46; CP.47